Inhibition of transient receptor potential vanilloid 1 (TRPV1) by a novel selective antagonist for anti-nociceptive effect on inflammatory pain without hyperthermia - Jialiang Guan; Chenru Zhao; Qiqi Zhou; Chao Zhu (PLoS ONE, 2026)
Nowadays, chronic pain remains a major clinical challenge because of the unsatisfactory efficacy and nonnegligible side effects of current treatments. Pharmacological antagonists of the transient receptor potential vanilloid-1 (TRPV1) channel for chronic pain relief have been confirmed in numerous preclinical studies. However, no TRPV1 antagonist has been approved in clinical, indicating an urgent need to develop effective TRPV1 antagonists with analgesic properties. In this study, we reported a TRPV1 antagonist 1-(1 H -indazol-4-yl)-3-((2-(4-methylpiperidin-1-yl)-6-(trifluoromethyl)pyridin-3-yl)methyl)urea named IMTU. According to the whole-cell patch clamp recording assay, we identified that IMTU was a potent and selective TRPV1 antagonist with an IC 50 value of 128.34 ± 9.49 nM and exciting no inhibition of cardiotoxicity-related channels. Further single-channel recording assay revealed that IMTU (300 nM) reduced the channel open probability from 80.8 ± 2.1% to 14.9 ± 2.8% with the presence of capsaicin (100 nM). In addition, does-dependent administration of oral IMTU alleviated nociceptive reactions on mouse models of formalin and inflammatory pain induced by complete Freund’s adjuvant (CFA) without hyperthermia. Finally, studies on molecular docking combined with site-directed mutagenesis suggested that residue Thr550 was critical for the TRPV1 antagonist by IMTU. Taken together, we identified a novel and selective TRPV1 antagonist IMTU exhibiting analgesic properties in mice, which provide a useful lead for the development of analgesia in the future.